Redox-Dependent Processes in Blood Plasma, Neutrophils and Erythrocytes of Patients with Ovary Cancer after Polychemotherapy by CAP Scheme - T. P. Gening; T. V. Abakumova; D. R. Dolgova; I. I. Antoneeva (Антибиотики и Химиотерапия)
The dynamics of the redox-dependent processes in blood plasma, neutrophils and erythrocytes of the patients with ovary cancer of the IIIrd clinical stage by FIGO after polychemotherapy according to the CAP scheme is considered. In the blood plasma and erythrocytes there were estimated the values of protein oxidative modification: carbonyl derivatives at λ=346 nm, 370 nm, 430 nm and 530 nm; the lipid peroxidation parameters: malonic dialdehyde, dienic conjugates, ketodiens, shiffs bases; the fermentative chain of the antioxidant system: activities of catalase, glutationtransferase and superoxide dismutase. In the peripheral blood neutrophils there were cytochemically determined the myeloperoxidase activity and the number of the active neutrophils in the spontaneous NBTR-test. After the polychemotherapy there were detected higher levels of the protein oxidative modification products and the products of the lipid peroxidation in the blood plasma and erythrocytes of the patients. Simultaneous increase of the activity of the antioxidant enzymes in the blood plasma could be evident of a high level of the lipid antioxidants peroxidation system functioning, whereas the simultaneous decrease of the activity of the antioxidant enzymes in the erythrocytes was indicative of passible development of oxidative stress in them. After the chemotherapy there was observed a significant and reliable decrease of the total number of the neutrophils. After the second course of the chemotherapy the activity of myeloperoxidase in them in the spontaneous NBTR-test as well decreased. Such a dynamics of the redox-depended processes in various components of the blood in the tumour carrier was characteristic of the tumor biological picture and required the use of differential multicomponent antioxidant therapy in patients with ovary cancer.